Direito & literatura: aspectos jurídicos e sociais na obra de Leandro Gomes de Barros - Damaceno, Elon da Silva Barbosa (2019)
Based on the assumption that literature can serve as a foundation for the legal world for the purpose of interpreting its reality, this research aims to study how Law is treated in the work of the popular poet Leandro Gomes de Barros, who initiated the editorial movement of the Brazilian cordel, with leaflets and romances that thought the social and political issues of his time. This work has as specific objectives to study about the increasingly latent need of the juridical approach more closely to the social reality, transcending the isolation resulting from the culture of Bachalerism degree; and consider the importance of the phenomenon being approached from its points of intersection with art, in this case, popular literature, leading the Right to raise what their dogmatic books lack, sensibility. Although there is not yet a specific theory in Brazil to trace the union between Law & Literature, the study works with the hypothesis that it’s possible to analyze the cordel leaflets produced by the poet from a legal point of view, shaping the innovative character of this text. It’s with this motivation that the work reflects on the necessity to study the Law starting from a nondogmatic vision; questions the connection between the field of literature and law, especially when it comes to the presence of this in that; while also analyzing the role of the literary genre as an art participant in communication and reflection on the needs of the people.